2002
DOI: 10.1046/j.1365-2036.2002.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind comparison of balsalazide, 6.75 g daily, and sulfasalazine, 3 g daily, in patients with newly diagnosed or relapsed active ulcerative colitis

Abstract: Background: Sulfasalazine is well established in the treatment of active ulcerative colitis. Intolerance to sulfasalazine, however, is a common problem. Balsalazide has been designed to deliver 5‐aminosalicylic acid to the colon without the poor tolerability of sulfasalazine. Aim: To compare the safety and efficacy of balsalazide, 6.75 g daily, with sulfasalazine, 3 g daily, in the treatment of active ulcerative colitis of all grades of severity. Methods: Balsalazide and sulfasalazine were compared in a multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 19 publications
(22 reference statements)
0
23
0
Order By: Relevance
“…Thus, 20 trials were included in the analysis (Fig. 1) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Of these 20 studies, 19 obtained acceptable Jadad score of 3 or more [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, 20 trials were included in the analysis (Fig. 1) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Of these 20 studies, 19 obtained acceptable Jadad score of 3 or more [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of this study show equal efficacy of SSZ in remission induction and maintenance therapy comparing with mesalamine and olsalazine. For balsalazide, the number of studies considered eligible was few and only two [22,23] and one study [35] were included for overall improvement and maintenance of remission, respectively. Although, there was no difference between balsalazide and SSZ in remission induction or maintenance therapy, the small number of studies does not allow a firm conclusion to be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the efficacy and tolerance of balsalazide with sulfasalazine (SSZ) it has been shown that the rate of relapse [24] and induction of improvement [25,26] was not significantly different for these two drugs but balsalazide was better tolerated and led to fewer withdrawals because of adverse events compared with SSZ [23][24][25][26]. This can be explained by much lower systemic absorption of the balsalazide carrier molecule, 4-aminobenzoyl-b-alanine, compared with the carrier molecule of SSZ, sulfapyridine, known to have significant systemic absorption.…”
Section: Efficacymentioning
confidence: 99%
“…Treatment of UC and CD varies depending on subtype and severity, but significant overlap is seen. The most common therapeutic agents for IBD, aminosalycilates and corticosteroids, have been incorporated into different dosage forms and drug delivery systems (DDS) in order to accomplish successful topical delivery of these agents at the site of inflammation (in CD -terminal ileum, or colon, the site of inflammation for both subtypes) (Green et al, 2002;Haddish-Berhane et al, 2007;Sands, 2007). The most critical step in the development of a reliable DDS for IBD treatment is to achieve improved localization and controlled release of the active substance at the site of inflammation, minimizing the premature release and subsequent absorption in the blood stream.…”
Section: Introductionmentioning
confidence: 99%